RCT to analyse efficacy of double port extension tubing connection to peripheral IV cannula in prevention of neonatal late onset sepsis - Malik, Vinit; Agrawal, Archana; Singh, Abhishek; Gupta, Navratan; Rathi, Alpha (International Journal of Contemporary Pediatrics, 2025)
Background: Late-onset sepsis (LOS), defined as sepsis occurring after 72 hours of age, causes substantial mortality and morbidity in neonates admitted in NICU. These neonates depend significantly on vascular access to administer fluids, nutrition, blood products and medication. This typically relies on the use of Peripheral Intravenous Cannula (PIVC) however, problems associated with IV infusion therapy include contamination of fluid with bacteria, endotoxins and particulates. Despite strict adherence to hygienic protocols, the incidence of nosocomial sepsis remains high. Incorporating an intravenous cannula with double port extension may be an effective strategy to reduce LOS. So, we did an open-label randomized controlled trial (RCT) to determine if the addition of a double port extension to an intravenous cannula can help in the prevention of LOS. Methods: Open label randomized controlled trial was conducted in 300 newborns admitted in the Department of pediatrics, LLRM Medical college, Meerut from April 2023 to March 2024. Admitted neonates underwent a sepsis screen. Those with a negative sepsis screen were enrolled and then randomly assigned to the groups. Group A: Babies with an intravenous cannula with a double port extension; Group B: Babies with an intravenous cannula without double port extension Results: 150 babies from each group were analysed. 13.34% and 43.34% were blood culture positive in each group respectively (p-value<0.001). 10% and 30% were sepsis screen positive in respective groups. 142 (94.67%) discharged, 1 (0.66%) expired and 133 (88.67%) discharged, 10 (6.66%) expired out of 150 babies in each group respectively. Conclusions: The addition of a double port extension in the IV cannula shows a reduction in LOS when compared to the control.